IKLIM KOMUNIKASI ORGANISASI YANG EFEKTIF DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT WARA KOTA PALOPO - Junaid Syah (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
Work motivation and tenure of employees in the organization have a very big influence on the organizational communication climate. The purpose of this study was to determine the influence of organizational communication climate at the Palopo City Wara Sub-district Office in improving employee performance. The research method uses descriptive qualitative research. Determination of informants in this study using purposive sampling technique, namely the method of determining the appropriate sample on certain criteria in accordance with the information required. The data analysis technique used interactive qualitative. The results showed that the organizational communication climate carried out by the Wara Head Office of Palopo City used open communication and was implemented in three ways, namely the technical meeting which is held once a month, employee participation and cooperation. between employees in each division.